Antibodies to neutralising epitopes synergistically block the interaction of the receptor‐binding domain of SARS‐CoV‐2 to ACE 2. Issue 3 (7th March 2021) - Pandey, Manisha; Ozberk, Victoria; Eskandari, Sharareh; Shalash, Ahmed O; Joyce, Michael A; Saffran, Holly A; Day, Christopher J; Lepletier, Ailin; Spillings, Belinda L; Mills, Jamie‐Lee; Calcutt, Ainslie; Fan, Fan; et al.
Abstract: Objectives: A major COVID‐19 vaccine strategy is to induce antibodies that prevent interaction between the Spike protein's receptor‐binding domain (RBD) and angiotensin‐converting enzyme 2 (ACE2). These vaccines will also induce T‐cell responses. However, concerns were raised that aberrant vaccine‐induced immune responses may exacerbate disease. We aimed to identify minimal epitopes on the RBD that would induce antibody responses that block the interaction of the RBD and ACE2 as a strategy leading to an effective vaccine with reduced risk of inducing immunopathology. Methods: We procured a series of overlapping 20‐amino acid peptides spanning the RBD and asked which were recognised by plasma from COVID‐19 convalescent patients. Identified epitopes were conjugated to diphtheria‐toxoid and used to vaccinate mice. Immune sera were tested for binding to the RBD and for their ability to block the interaction of the RBD and ACE2. Results: Seven putative vaccine epitopes were identified. Memory B‐cells (MBCs) specific for one of the epitopes were identified in the blood of convalescent patients. When used to vaccinate mice, six induced antibodies that bound recRBD and three induced antibodies that could partially block the interaction of the RBD and ACE2. However, when the sera were combined in pairs, we observed significantly enhanced inhibition of binding of RBD to ACE2. Two of the peptides were located in the main regions of the RBD known to contact ACE2. Of significant importance to vaccine development, two of the peptides were in regions that are invariant in the UK and South African strains. Conclusion: COVID‐19 convalescent patients have SARS‐CoV‐2‐specific antibodies and MBCs, the specificities of which can be defined with short peptides. Epitope‐specific antibodies synergistically block RBD–ACE2 interaction. Abstract : We identified SARS‐COV‐2 receptor‐binding domain (RBD)‐specific antibodies in convalescent patients, specificities of which could be defined with short peptides. These peptides when used as immunogens, induced neutralising antibodies which synergistically blocked RBD and ACE 2 interaction. Our approach will aid the design of a vaccine containing minimal antigenic material, thus improving the vaccine's safety profile.